KONSTRUKSI SOSIAL PERNIKAHAN ANTAR SUKU DALAM MASYARAKAT MUSLIM INDONESIA ANALISIS HUKUM ISLAM DAN BUDAYA LOKAL - Najmus Shobah Al-mutanaffas; Muhammad Zainuddin Sunarto (USRAH: Jurnal Hukum Keluarga Islam, 2026)
The social construction of interethnic marriage by analyzing how customary norms, cultural practices, Islamic law, and principles of legal philosophy interact in shaping the social legitimacy of such marriages in Indonesia. The purpose of this research is to understand how society interprets values, norms, and cultural identities in interethnic marriage practices, as well as how the philosophical foundations of law such as justice, freedom, and public benefit provide normative support for their acceptance. Using a qualitative approach through literature analysis, the study finds that interethnic marriage produces a dual social construction: it is viewed both as a form of social integration and as a source of cultural resistance related to lineage, adherence to customary norms, and group identity. Customary law functions as a strong social regulator through rituals, symbolic values, and social sanctions, while Islamic law permits interethnic marriage as long as the fundamental legal conditions of marriage are fulfilled. Philosophically, however, law requires a balance between respecting tradition, ensuring substantive justice, and protecting individual rights to choose a spouse. Field findings show that value conflicts regarding gender roles, communication patterns, and childrearing practices demand continuous social and ethical negotiation. Overall, interethnic marriage represents an arena where traditional values and legal philosophical principles converge, requiring harmony between culture, legal norms, and family welfare.